2015
DOI: 10.1097/aci.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis in adolescents

Abstract: To be successful, anaphylaxis management strategies require more multidimensional approaches among adolescents. We propose a tripartite management framework that emphasizes integration of the following components: better understanding of adolescence; incorporation of the constituents of adolescents' social networks; and adolescent-tailored healthcare perspectives. This theoretical framework now requires translation into an intervention, feasibility and pilot testing, and formal evaluation through randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Despite a diagnosed allergy and prescribed EAI, the World Allergy Organization noted the compliance rates of patients and caregivers carrying EAIs and remaining competent in their use decreases significantly over time (Simons et al, 2013). This is a particular problem with adolescents where the risk of anaphylaxis morbidity and fatality is disproportionately high (Greenhawt et al, 2018;Nwaru & Sheikh, 2015). Spina, McIntyre, and Pulcini (2012) found that only half of adolescents prescribed an EAI carried an unexpired auto-injector.…”
Section: Stock Eais In the School Settingmentioning
confidence: 99%
“…Despite a diagnosed allergy and prescribed EAI, the World Allergy Organization noted the compliance rates of patients and caregivers carrying EAIs and remaining competent in their use decreases significantly over time (Simons et al, 2013). This is a particular problem with adolescents where the risk of anaphylaxis morbidity and fatality is disproportionately high (Greenhawt et al, 2018;Nwaru & Sheikh, 2015). Spina, McIntyre, and Pulcini (2012) found that only half of adolescents prescribed an EAI carried an unexpired auto-injector.…”
Section: Stock Eais In the School Settingmentioning
confidence: 99%
“…Patients/carers may benefit from an anaphylaxis management plan which can also be shared with school, work, etc. [ 30 ] with clear written instructions of how to manage an acute attack [ 1 ••, 2 ••, 3 ••, 4 ••]. It is important to clearly record the diagnosis in the patient’s notes and wearing emergency jewelry (e.g., a MedicAlert bracelet) should be encouraged [ 1 ••, 2 ••, 3 ••, 4 ••] so as to alert first-responders to administer epinephrine.…”
Section: Treatmentmentioning
confidence: 99%